2019
DOI: 10.3390/ijerph16245043
|View full text |Cite|
|
Sign up to set email alerts
|

Cytotoxicity Assessment of PM2.5 Collected from Specific Anthropogenic Activities in Taiwan

Abstract: Fine particulate matter (PM 2.5 ) from different sources with different components have different health impact. In this research in Taiwan, composition and cytotoxicity of PM 2.5 from long-range transport event (LRT), traffic activity, and outdoor cooking at night market were studied. The PM 2.5 mass concentrations were 39.0 µg/m 3 during LRT, 42.9 µg/m 3 at traffic area, and 28.3 µg/m 3 at the night market. Traffic area had highest concentrations of PCDD/Fs (46.9 fg I-TEQ/m 3 ) when highest PAH concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Health impacts related to unsafe air quality have been the subject of many studies, and focus on correlating particulate matter concentrations and premature mortality as well as related economic losses [ 8 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Some of these studies were performed using Thai populations [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Health impacts related to unsafe air quality have been the subject of many studies, and focus on correlating particulate matter concentrations and premature mortality as well as related economic losses [ 8 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Some of these studies were performed using Thai populations [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study of PM 2.5 in northern Taiwan, the results showed that traffic activity generates higher PM 2.5 concentration (mg/m 3 ) than long-range transport events and outdoor cooking (night market) 28 . The potential factors influencing the PM 2.5 composition in vehicle emissions include fuel type, engine age, running distance, vehicle displacement (c.c.…”
Section: Discussionmentioning
confidence: 85%
“…The aqueous extracts of PM 2.5 samples were filtered using a glass syringe and a 20 mm polytetrafluoroethylene (PTFE) filter (Advantec Toyo Kaisha, Ltd., Tokyo, Japan). The filtrate was subjected to ion chromatography using Dionex ICS-1000 (Thermo Fisher Scientific Inc., Waltham, MA, USA) to determine the ionic content (recovery range of 88–104%) 28 with a detection limit of 0.01–10.1 µg.…”
Section: Methodsmentioning
confidence: 99%
“…[11] Different cell lines were used, depending on the environment assessed and exposure routes implicated. The A549 alveolar epithelial cell line was used in four outdoor environment studies [12,13] and for occupational exposure in the waste sorting industry [11,14]. Lymphocytes were used in two studies of occupational and outdoor environments [15,16].…”
Section: Cytotoxicity Of Filtering Respiratory Protective Devices Fro...mentioning
confidence: 99%